Confessional Model of Image of Person in Text of Old Believer Popular Print “Two roads — Two ways” - E. V. Bykova; О. M. Valova (Научный диалог)
The article is devoted to the analysis of the confessional model of the image of a person in the popular prints of Old Believers-chapels of the Yenisei “Two Roads — Two Ways”. The novelty of the research is due to the introduction of new sources into scientific circulation. The relevance of the work lies in the appeal to the modern processes of artistic creation in the Old Believer environment of chapel communities. The material for the study was the texts of popular prints and spiritual literature, which were created among the Old Believers-chapels of Siberia, collected in the expeditions of 2018—2021 on the Yenisei in the Old Believer communities of chapel accord. The visual and verbal means of embodying ideas about the sinfulness of the modern world, subjecting people to temptations, about the correct life scenario of a person belonging to a closed Old Believer community, are analyzed. It is noted that the image and the text form a unity and serve to confirm the concept of the life of the community member. In addition to the print “Two Roads — Two Ways”, the verses “Think, a poor man” and “Motivation to fight against sin” were analyzed. The authors come to the conclusion that the verbal and visual components of the studied works represent the values of the Old Believer communities, which make it possible to characterize them as marginal, closed, traditionalist and eschatological.